31. FLAVONOID INHIBITORS OF XANTHINE OXIDASE IN THE TREATMENT OF GOUT: AN OVERVIEW (Vietnam Journal of Community Medicine, 2024)
Flavonoids are naturally occurring phenolic compounds, which are active ingredients that are abundantly supplemented from the diet. Flavonoids have attracted special attention from researchers due to their safety, efficacy, and low side effects in inhibiting xanthine oxidase (XO) in the treatment of Gout. Many flavonoids show the ability to inhibit XO similar to allopurinol. In this review, studies on inhibition of XO activity and Gout treatment of flavonoids are analyzed and evaluated from the aspects of chemical structure relationship and biological effects. The results indicated that hydrophobic interactions were important in binding flavonoids to XO. The ability to inhibit XO increases when the hydrophobic interaction affinity increases in flavone and flavanol groups. In particular, the planar with C2=C3 double bonds on the ring C and benzopyran ring of flavonoids are beneficial for competitive binding to the substrate of XO and inhibition of XO. Furthermore, the article also provides new perspectives on the limitations of current research aimed at promoting the development and in-depth application of flavonoids.
Keywords: Acid uric; flavonoid; xanthin oxidase